Financing small and medium-sized enterprises in Thailand: The importance of bank loans and financing diversification - Harri Ramcharran (The Journal of Entrepreneurial Finance (JEF), 2017)
Bank loans are the main sources of financing the Small and Medium-Sized Enterprises (SME) sector of the Thai economy. This sector contributes to about 37% GDP and employs about 80% of the labor force. Recent data indicate a decline in bank lending; this necessitates the efficient use of available funds and strategies to diversify SME financing. Using data from 2007 - 2014, we analyze the performance of this sector by applying several measures of productivity. We find average productivity to be greater than one for: (a) SME output per unit of SME and (b) SME output per Baht loan. This satisfactory performance is the result of government stabilization policies to ensure adequate loan support to this sector together with effective risk management strategies. The decline in the ratio of SME nonperforming loans to total SME loans attests to prudent policies to maintain high asset quality during a period of economic fluctuation. Policies to supplement bank financing and to diversify the sources of funding include the widening and deepening of the capital market. Sustainable growth policies should emphasize human capital development to stem declining labor productivity and also increasing expenditures on R&D to promote innovation-led growth.
Keywords: E44; E65; G28; G21; 650; small and medium-sized firms; bank loans; productivity; efficiency